2016
DOI: 10.1016/j.bbagen.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Ionization basis for activation of enzymes soluble in ionic liquids

Abstract: We can conclude that ionizing-dissociating abilities of an IL can be used as a basis for predicting the activity of enzymes soluble in the IL. General significance Ionization basis for activation of enzymes gives a deeper understanding of the behavior of enzymes in non-aqueous media at a molecular level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Thus, anhydrous ILs were shown to solubilize dry proteins by forming surfactant nanostructures, 761 and ionization properties of IL were suggested to be responsible for the enzyme activation (Figure 23). 762 According to a theoretical study on lipase B from Candida antarctica (CAL-B), the enzyme formed Coulomb interactions with the IL anions and van der Waals interactions with the cations; the ions, which formed strong hydrogen bonds with the enzyme, promoted conformational changes in the protein, leading to its denaturation. The butyl group of the [C 4 MIM] + cation was able to penetrate into the active site of the lipase, possibly inhibiting its activity.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Thus, anhydrous ILs were shown to solubilize dry proteins by forming surfactant nanostructures, 761 and ionization properties of IL were suggested to be responsible for the enzyme activation (Figure 23). 762 According to a theoretical study on lipase B from Candida antarctica (CAL-B), the enzyme formed Coulomb interactions with the IL anions and van der Waals interactions with the cations; the ions, which formed strong hydrogen bonds with the enzyme, promoted conformational changes in the protein, leading to its denaturation. The butyl group of the [C 4 MIM] + cation was able to penetrate into the active site of the lipase, possibly inhibiting its activity.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…However, for increasing activity, Ou and co-workers reported that introduction of hydroxyalkyl moiety in anion or cation of ILs was effective to improve activity, though the resulting ILs have been generally hydrophilic. 342 Since deep eutectic solvent (DES) 343−346 ) which has hydroxyethyl moiety, just addition of DES solvent affected the lipase activity, although the effect significantly depended on the contents. Kim and co-workers reported that a combination of [Chol] with urea and glycerol improved activity, while those of formamide and glycerol and foramide and thiourea caused a drop in the activity.…”
Section: Activation Of Lipases By the Design Of Ils As Solventmentioning
confidence: 99%
“…From the standpoint of easy workup, hydrophobic ILs are preferable. However, for increasing activity, Ou and co-workers reported that introduction of hydroxyalkyl moiety in anion or cation of ILs was effective to improve activity, though the resulting ILs have been generally hydrophilic . Since deep eutectic solvent (DES) contained cholinium cation ([Chol]) which has hydroxyethyl moiety, just addition of DES solvent affected the lipase activity, although the effect significantly depended on the contents.…”
Section: Enzymes Activated By Ionic Liquids For Organic Synthesismentioning
confidence: 99%
“…Building further on the seminal work of Walker and Bruce, a wide variety of designer ILs and PILs have been described that contain hydroxyl 110,111,112 or alkoxyl 76,113,114,115,116,117,118 groups to enable sustainable biocatalysis. More recently, some basic principles were proposed by the group of Ou 119 as a guide for the successful design of biocompatible ILs in which enzymes dissolve and maintain their activity.…”
Section: Figure 8 Enzymatic Oxidation Of Codeine In An Ilsmentioning
confidence: 99%
“…Two series of biocompatible ILs -hydroxyalkyl imidazolium hydroxyalkyl sulfonates, and 3-hydroxypropyl-tri-(2hydroxyethyl) ammonium hydroxylalkyl sulfonates (see Figure 9 for structures) were designed and synthesized based on these principles. They were subsequently tested for compatibility with lipases from C. Antarctica and P. cepacia in the transesterification of 1-butanol at 50 0 C. 119 The lipases dissolved in these ILs and the resulting activities were comparable to those observed in water under the same conditions.…”
Section: Figure 8 Enzymatic Oxidation Of Codeine In An Ilsmentioning
confidence: 99%